PERAN KAMPANYE SOCIAL MARKETING TERHADAP KEPUTUSAN MASYARAKAT UNTUK MEMBAYAR ZAKAT MELALUI LEMABAGA AMIL ZAKAT - SIGIT INDRAWIJAYA (Jurnal Manajemen Terapan dan Keuangan, 2016)
The low effectiveness of zakat distribution nowaday is related to the lack of interest of the community to pay zakat through zakat institutions. This is indicated by collection and distribution of zakat which is less managed. This eventually leads to the purpose of zakat in welfare of society which is not achieved. Social marketing campaigns as one marketing element  can be used as an alternative in changing people's behavior in paying zakat through Amil Zakat Institution. This study was aimed to measure the impact of social marketing campaigns of zakat payment via Amil Zakat on the decision of  community in paying zakat through the Institute amil zakat. Method used in this research was quantitative descriptive. Data were analyzed using simple linear regression analysis with social marketing campaign variables as independent variable and decisions in pay zakat through amil institutions as the dependent variable.  Results showed that social marketing campaign had positive influence on the community's decision to pay zakat through Amil Zakat